Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1093/icvts/ivy037
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for spinal cord ischaemia after thoracic endovascular aortic repair

Abstract: Sufficient perioperative care should be given to high-risk patients who have endografts that cover more than 9 segments and endografts that cover segments from Th8 to Th12. Adequate haemoglobin levels and mean arterial pressure are needed to provide sufficient spinal cord perfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…Other risk factors for SCI, as described in published reports, include prior aortic repair, perioperative hypotension (mean arterial pressure <70 mmHg), COPD, and single-stage procedure. 27 , 28 In our study, we consciously avoided these risk factors of SCI. As shown in Tables 1 and 2 , there were fewer patients with advanced age, previous aortic repair, COPD, and LSA coverage in the TEVAR+Cuff group ( P >0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Other risk factors for SCI, as described in published reports, include prior aortic repair, perioperative hypotension (mean arterial pressure <70 mmHg), COPD, and single-stage procedure. 27 , 28 In our study, we consciously avoided these risk factors of SCI. As shown in Tables 1 and 2 , there were fewer patients with advanced age, previous aortic repair, COPD, and LSA coverage in the TEVAR+Cuff group ( P >0.05).…”
Section: Discussionmentioning
confidence: 99%
“…9 10 Other risk factors for the development of PSCI, which can represent relative indications for HGA preservation, are young age, left ventricular dysfunction, severe atherosclerotic disease of the superior mesenteric artery or the ipsilateral CFA or contralateral HGA, and presence of a large patent inferior mesenteric artery. 11 In a recent review, it was shown that higher rates of PSCI seem to be associated with extensive endovascular procedures, particularly with concomitant thoracic aneurysm repair, even when only a single collateral was occluded. 12 In that sense, preservation of HGA perfusion is important to minimize the risk of spinal cord injury because its patency significantly reduces the incidence of PSCI after extensive aortic endografting.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Indications for CSF drain placement included: all patients being treated with TEVAR (n ¼ 1), all patients being treated with TEVAR without specific contraindications (n ¼ 1), and patients determined by the authors to be high risk for SCI (n ¼ 6). 3,[11][12][13][14][15][16][17] Methods of risk stratification varied between studies but generally were based on the size of the aneurysm and/or involvement of branching or segmental arteries.…”
Section: Protocol and Indication For Csfdmentioning
confidence: 99%
“…Seven of 8 protocols for CSF drainage involved drainage of CSF to a target pressure, between 7 and 12 mm Hg. 3,11,[13][14][15][16][17] Three had limits of CSF volume drained, of 10 to 20 mL/h. 11,12,16 Three studies lowered the target CSF pressure if symptoms of SCI became evident.…”
Section: Protocol and Indication For Csfdmentioning
confidence: 99%
See 1 more Smart Citation